The effect of exercise interventions on reducing the risk of depressive and cognitive disorders in post-stroke—a systematic review and meta-analysis - Yang, Zixian; Qin, Shaokun; Li, Jiaxing; Li, Cong; Lu, Ye; He, Pei; Liu, Jia; Pei, Lin (Frontiers in Neurology, 2025)
BackgroundStroke patients often experience sequelae such as depressive symptoms, cognitive impairment, and abnormal physical function. Exercise intervention may be an effective and safe non-drug treatment to address these health issues.ObjectiveThe aim of this meta-analytical review was to explore the effects of exercise intervention programs on depressive symptoms, cognitive function, physical function, and quality of life in stroke patients, as well as to identify appropriate exercise programs.MethodsSeven databases were searched from the library’s construction until 30 August 2024. A meta-analysis was performed, and the risk of bias was assessed using Review Manager 5.4. Sensitivity analysis was conducted using Stata 16.0 software, and the overall certainty of the evidence was rated using Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) methods.ResultsA total of 11,607 studies were identified. Among these, 20 studies, which included 1,848 patients, were considered eligible for this network meta-analysis. Compared to the control group, exercise significantly improved cognitive function (standard mean difference [SMD] = 1.08, 95% confidence interval [CI] = 0.40–1.75, p = 0.002), physical balance ability (mean difference [MD] = 0.80, 95% CI = 0.23–1.37, p < 0.01), physical walking ability (MD = 48.39, 95% CI = 8.06–88.72, p = 0.02), and quality of life. However, exercise had no significant effect on depressive symptoms (SMD = −0.2, 95% CI = −0.46–0.05, p = 0.11). A subgroup analysis indicated that a longer duration of exercise (> 3 months) can effectively improve depressive symptoms in stroke patients.ConclusionThe results indicated that cognitive function, balance, walking speed, and quality of life of stroke patients improved following exercise intervention, and longer exercise duration (> 3 months) contributed to alleviating the depressive symptoms of stroke patients. Therefore, we recommend that stroke patients engage in physical exercise 3 times a week for 1 h each session. The exercise duration should continue for at least 3 months to ensure the best therapeutic effect. Furthermore, determining exercise intensity should be a personalized process—carefully customized to align with the physical capabilities and limitations of each patient.Systematic review registrationhttps://www.crd.york.ac.uk/prospero, CRD42024520778.